Multiscale Control of Nanocellulose Assembly: Transferring Remarkable Nanoscale Fibril Mechanics to Macroscale Fibers - Mittal, Nitesh; Ansari, Farhan; Gowda.V, Krishne; Brouzet, Christophe; Chen, Pan; Larsson, Per Tomas; Roth, Stephan V; Lundell, Fredrik; Wågberg, Lars; Kotov, Nicholas A; Söderberg, L. Daniel (ACS nano, 2018)
Nanoscale building blocks of many materials exhibit extraordinary mechanical properties due to their defect-free molecular structure. Translation of these high mechanical properties to macroscopic materials represents a difficult materials engineering challenge due to the necessity to organize these building blocks into multiscale patterns and mitigate defects emerging at larger scales. Cellulose nanofibrils (CNFs), the most abundant structural element in living systems, has impressively high strength and stiffness, but natural or artificial cellulose composites are 3–15 times weaker than the CNFs. Here, we report the flow-assisted organization of CNFs into macroscale fibers with nearly perfect unidirectional alignment. Efficient stress transfer from macroscale to individual CNF due to cross-linking and high degree of order enables their Young’s modulus to reach up to 86 GPa and a tensile strength of 1.57 GPa, exceeding the mechanical properties of known natural or synthetic biopolymeric materials. The specific strength of our CNF fibers engineered at multiscale also exceeds that of metals, alloys, and glass fibers, enhancing the potential of sustainable lightweight high-performance materials with multiscale self-organization.